Islamization of Science Ismail Raji al-Faruqi and Integration-Interconnection of Science Amin Abdullah: A Comparative Study - Syihabuddin, Muhammad; Soleh, Achmad Khudori; Mursyid, Achmad Yafik (University of Darussalam Gontor, Indonesia, 2024)
The discourse on the dichotomy of modern science and Islamic science is an interesting topic of discussion and is always debated by Muslim scientists. Some of them, namely Ismail Raji al-Faruqi and Amin Abdullah, are trying to respond to and solve problems that occur in the scientific realm. Al-Faruqi initiated the Islamization of science which seeks to unify the two sciences (science and Islam). Likewise, Amin Abdullah with his integration-interconnection paradigm also offers an open dialogue between the two sciences. Then this research aims to look at the structure of thought between the two figures mentioned, as well as looking for common threads related to the similarities and differences in the ideas of science integration being promoted. This research uses library research methods through several textual sources related to the topic discussed, primarily in the form of books by the two figures studied, and secondary in the form of scientific articles that have related themes. The results of this article are: 1) The Islamization of al-Faruqi's knowledge leads to the relevance between science and Islam, science is Islamized through twelve concrete steps based on the concept of monotheism. 2) Amin Abdullah's ideas regarding integration-interconnection can be seen from the spider web framework which emphasizes mastery of various sciences, both modern science and Islamic science. 3) The similarities in thinking between the two can be seen through the spirit in answering scientific dichotomies. The difference is, that al-Faruqi emphasized mastery of modern knowledge (science) to then be converted to Islam to conform to the pattern of monotheistic teachings. Meanwhile, Amin Abdullah's ideas emphasized mastery of general science and Islam. So that each scientific group is aware of its limitations and shortcomings so that they can complement and complement each other